Electrically Conductive Polyester Fabrics Embedded Polyaniline - Nurzatul Ikma Omar, Siti; Zainal Ariffin, Zaidah; Mad Akhir, Rabiatuladawiyah; Izzharif Abd Halim, Mohamed; Ramli, Rosmamuhamadani; Muzamir Mahat, Mohd (International Journal of Engineering and Technology, 2019)
Recently, conductive fabric has attracted massive attention among researchers due to their unique conductive properties with a wide range of possible applications. This study explores the fabrication of poly aniline (PANI) conductive fabric through an immersion technique of polyester fabric in PANI solution. Two types of acids (sulphuric acid (H2SO4) and p-toulene sulfonic acid (pTSA) have been employed as the doping agent to induce the conductivity in various weight percentages (0.3, 0.6 and 0.9 wt%) with immersion time of 5, 10 and 15 minutes. The fabricated conducting fabrics were then characterized by Fourier Transform Infrared Spectroscopy with attenuated total reflection (FTIR-ATR) and X-ray Diffraction (XRD) for analyses of chemical structure and phase identification respectively. Their morphologies were observed by Scanning Electron Microscope (SEM) which revealed the various fibrous structure. The finding is in line with the electrical conductivity properties of the fabrics observed using Four-point probe technique. Optimum conductivity of the conductive fabrics were found to be at 0.6 wt. % for both types of acid which are 1.30 x 10-2 S/cm (H2SO4) and 1.39 x10-3 S/cm (pTSA). Meanwhile, the varied immersion time showed no significant changes on this property, due to the short time laps. For FTIR results, the peaks confirmed the presence of PANI-EB together with the introduced acid within the PANI backbone. Collectively, H2SO4 is found to be a good candidate as doping agent, deduced from obtained conductivity values and structural properties.Â Â